Thermal Stress Markers of Ongole Cattle in Transitional Phase: THI and HSP70 - Dhan, Priyanka; Seshu Kumari, Vasantha; Gollu, Chaitanya; Swaroop Murikipudi, Naveen; Srikanth Nistala, Raghavendra (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The effect of environment on the health and productivity of the animals is well evidenced in different species of animals. Indigenous cattle were thought to be tolerant and well adapted to environmental changes, but still the effects of varying THI during the transition period has not been explored so far in connection with the expression of stress biomarkers like heat shock proteins particularly in indigenous breeds like Ongole. The present study investigated the gene expression of heat shock proteins (HSP70) in transitional Ongole cows, a dual-purpose indigenous breed from Andhra Pradesh, India. The study measured the relative mRNA expression of HSP70 in peripheral blood mononuclear cells (PBMCs) using the 2-ΔΔCq method. The results revealed significant changes in the parameters studied, providing insights into the stress adaptation mechanisms of Ongole cows during the transition period. It was noticed that, the day zero of parturition was found to be more stressful to the Ongole cows compared to antepartum and postpartum periods. Adoption of nutritional and summer management strategies might ameliorate the negative impacts of higher THI during transition period for optimum production and well-being of Ongole cattle.